The role of job satisfaction mediate on the effect of entrepreneurial leadership on organizational citizenship behavior - Asril, Akmil; Rahyuda, Agoes Ganesha (Linguistics and Culture Review, 2022)
The purpose of this study was to analyze the effect of entrepreneurial leadership and job satisfaction on organizational citizenship behavior, as well as to analyze the role of job satisfaction mediati the influence of entrepreneurial leadership on organizational citizenship behavior. The population in this study were employees of PT. BPR Lestari Bali totaled 409 people. The sample in this study were 124 respondents. This research uses PLS (Partial Least Square) analysis technique. The results show that entrepreneurial leadership has a positive and significant effect on organizational citizenship behavior. Entrepreneurial leadership has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on organizational citizenship behavior. Job satisfaction as a partial mediation or partial mediation on the influence of entrepreneurial leadership on organizational citizenship behavior, meaning that the independent variable is able to directly influence the dependent variable or indirectly by involving the mediator variable. A leader in a company needs to have a clear vision, be creative, innovative, responsible, and be able to motivate to create positive things for employees by increasing entrepreneurial leadership and job satisfaction so that their organizational citizenship behavior will also increase.